Do colonialismo ao fascismo : religiosidade e nacionalismo a partir da análise do Il Corriere d’Italia (Bento Gonçalves/RS 1913 – 1927) - Prá, Lino Alan Ribeiro da Luz Dal (2017)
Throughout the regional historiographical process, journalism has been widely used as an object of research, since through it it is possible to understand identitary, cultural and religious aspects of the societies in which it has been developed and reproduced for the masses, whether located in political centers of the State or in the colonial regions. Another use for these documents occurs when analyzing the ideological movements articulated by the editorials of these publications, that aim to lead the circulation of the news according to their particular interests. Regarding this, the present work seeks to interpret how the consolidation of the Italian collectivities in Bento Gonçalves and its surroundings occurred, besides analyzing its collective actions and regional and international interests between 1913 and 1927 through the newspaper Il Corriere d'Italia, publication that by its religious and nationalist character, eventually spread a different perspective on the relations between the Italian State and the Church, marked in other weekly newspapers as unfeasible, but recurrently encouraged by the scalabrinian segment, which owns the newspaper. Another significant point was centered in the analysis of the constant combat carried out by the Carlist Order against the National Fascist Party, which holds a relatively accepted ideology in the northeast of Rio Grande do Sul, made up of populations that accompanied the electoral escalation of the party's leaderships. However, before addressing these points, a study about the migratory processes articulated by the Italians in the nineteenth century, the development of their colonies in the state of Rio Grande do Sul, the articulation of the first ethnic publishers, and the consolidation of their opinions and cultural values will be made.